Evaluation of Earthquake Cloud Model By Estimating Correlation Coefficient Between Earthquake Events and Theirs Predictions in Iran at The Fourth Quarter of 2009 - Mohammadreza Mansouri Daneshvar; Aliasghar Barhaman; Parviz Mansouri Daneshvar (مخاطرات محیط طبیعی, 2012)
The earthquake cloud model has invited based on Zhonghao Shou researches at year 2004. His earthquake predictions for USGS office from 1994 to 2003 have confirmed that application of this model with P>72%. While, in our country has not exhibited scientific assessment of this model since present. The main aim of this paper is the evaluation of earthquake cloud model to predicting frequencies of earthquake events at the limited time period. For this purpose has determined the earthquake frequencies with M≥2.5 Richter at Iran.  For the compilation of database were used two references: meteorological satellite images with a half-hour time series and seismological bulletin of occurred earthquakes catalogue for months October to December 2009. Firstly were determined the earthquake clouds on meteorological satellite images for distinguished time period. Then earthquake clouds have geo-referenced in networking map of Iran using GIS with pixels 2×°2° in WGS coordinate system. Finally the correlation ratio between adapted of occurred earthquakes in the corresponding pixels with the density of earthquake clouds was showed significant rate R=0.837 and R2=0.7. Also the findings of this paper showed that the earthquake cloud model has the ability to forecasting 69% of all earthquakes in Iran with M≥2.5 Richter.